PENGARUH KUALITAS PRODUK DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN PADA 200 CAFE AND FOOD DI KOTA MALANG - Indah Yuni Wardani (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The intention of this research is to identify the influence of product quality and sales promotion toward repurchase decision which are indirectly mediated by customer satisfaction at 200 Café and Food in Malang city. This research is quantitative research. This study used accidental sampling with the analysis technique using descriptive statistics and SmartPLS 3.0 software. The result of the study showed that; There is positive and significant influence between product quality toward customer satisfaction directly, there is positive and significant influence between sales promotion toward consumer satisfaction directly, there is positive and significant impact between product quality toward repurchase decision, there is positive and significant impact between sales promotion toward repurchase decision, there is positive and significant impact between customer satisfaction on repurchase satisfaction, customer satisfaction can meadiate the impact of product quality toward repurchase decision, customer satisfaction can mediate the influence of sales promotion toward repurchase decision positively and significantly.